2018
DOI: 10.1093/schbul/sby130
|View full text |Cite
|
Sign up to set email alerts
|

Burden for Parents of Patients With Schizophrenia—A Nationwide Comparative Study of Parents of Offspring With Rheumatoid Arthritis, Multiple Sclerosis, Epilepsy, and Healthy Controls

Abstract: Parents of patients with schizophrenia have a considerably higher risk of psychiatric health care and social welfare benefit receipt than other parents. Psychiatric health care use worsens over time and with increasing disease severity of the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…The social perception of limited effectiveness for the medical treatment of psychosis and Alzheimer disease might support the special interest in preventive strategies. The chronic and severe impact of patients with both diseases on their families and caregivers might also explain the high interest in the prevention of these disorders [10,61,62]. The absence of established analytical or image criteria for the diagnosis of psychosis might also contribute to the limited interest in the diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The social perception of limited effectiveness for the medical treatment of psychosis and Alzheimer disease might support the special interest in preventive strategies. The chronic and severe impact of patients with both diseases on their families and caregivers might also explain the high interest in the prevention of these disorders [10,61,62]. The absence of established analytical or image criteria for the diagnosis of psychosis might also contribute to the limited interest in the diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, patients are encouraged to take an active role in the development of an active and meaningful life while growing beyond the misfortune of mental illness [8,9]. The traditional clinical and societal view of schizophrenia is of a debilitating and deteriorating disorder, with a poor outcome [10]. There is evidence of persisting stigma about mental illness that leads to negative stereotyping and to discriminatory behavior toward people with schizophrenia [11].…”
Section: Introductionmentioning
confidence: 99%
“…Better adherence may relieve parental concerns over discontinuation of medication use by their offspring and reduce the need for monitoring of medication taking behaviour 29 . Our previous study showed that parents of patients with schizophrenia in general have a higher risk of psychiatric health care use compared with parents of patients with MS, rheumatoid arthritis, epilepsy or healthy controls 31 .…”
Section: Discussionmentioning
confidence: 95%
“…In our previous study, we found that parents of patients with schizophrenia have a considerably higher risk of psychiatric health care use than parents of patients with multiple sclerosis (MS), rheumatoid arthritis, epilepsy or healthy controls 31 . Our recent observational studies have shown that LAIs were associated with lower risk of psychiatric re-hospitalizations compared with oral antipsychotics 32,33 although this is contrary to the results of randomized trials 34,35 .…”
mentioning
confidence: 99%
“…Family relationships are more likely to be asymmetric and involve negative or ambivalent feelings compared to the general population (Randolph, 1998) and, understandably, often become strained (Corcoran et al, 2007). Indeed, much existing research on the family context of psychosis focuses on the ‘burden’ of caring for a young person with psychosis, which can be considerable and may result in family members becoming psychologically distressed themselves (e.g., Fadden, Bebbington, & Kuipers, 1987; Mittendorfer‐Rutz et al, 2018). The argument for intervening to support families is clear (e.g., Addington, Collins, McCleery, & Addington, 2005).…”
Section: Introductionmentioning
confidence: 99%